Hydroxyl (OH) radical oxidation of surfactant films formed from woodland aerosol particulate material at the air-water interface - Edward J. Stuckey; Rebecca J.L. Welbourn; Tobias W.D. Robson; Connor R. Barker; Matthew Wilkinson; James I.L. Morison; Martin D. King (Atmospheric Environment, 2026)

Case–Case Comparison of Candida auris Versus Other Candida Species Bloodstream Infections: Results of an Outbreak Investigation in Colombia - Diego H. Caceres; Sandra M. Rivera; Paige A. Armstrong; Patricia Escandon; Nancy A. Chow; Maria Victoria Ovalle; Jorge Díaz; Gordana Derado; Soraya Salcedo; Indira Berrio; Andres Espinosa-Bode; Carmen Varón; et al. (Mycopathologia, 2020)

Pleistocene origin and population history of a neoendemic alpine butterfly - SEAN. D. SCHOVILLE; MATTHEW STUCKEY; GEORGE K. RODERICK (Molecular Ecology, 2011)
Alpine environments underwent dramatic transformation during glacial–interglacial cycles, with the consequence that geographical, ecological and demographic changes of alpine populations provided the opportunity for formation of neoendemic species. Several biogeographical models have been proposed to account for the unique history of alpine populations, with different expectations of genetic divergence and speciation. The expanding alpine archipelago model proposes that alpine populations expand spatially and demographically during glacial events, dispersing between mountain ranges. Under this model, alpine populations are unlikely to diverge in isolation due to substantial interpopulation gene flow. In contrast, the alpine archipelago refuge model proposes that gene flow during glacial phases is limited and populations expand demographically during interglacial phases, increasing genetic isolation and the likelihood of speciation. We assess these models by reconstructing the evolutionary history of Colias behrii , a morphologically and ecologically distinct alpine butterfly restricted to the California Sierra Nevada. C. behrii exhibits very low genetic diversity at mitochondrial and nuclear loci, limited population structure and evidence of population expansion. C. behrii and Rocky Mountain C. meadii share identical mitochondrial haplotypes, while in contrast, nuclear data indicate common ancestry between C. behrii and Cascades Range Colias pelidne . The conflict in gene genealogies may be a result of recent expansion in North American Colias, but an isolation with migration analysis indicates that genetic patterns in C. behrii might result from differential introgression following hybridization. Based on the timing of population expansion and gene flow between mountain ranges, the expanding alpine archipelago model is supported in C. behrii .